Clerodendranthus spicatus [Orthosiphon aristatus (Blume) Miq.] maintains uric acid homeostasis via regulating gut microbiota and restrains renal inflammation in hyperuricemic nephropathy - Wang, Yang; Li, Kaiwen; Yan, Siya; Li, Ge; Cheng, Meifang; Chen, Qian; Wu, Yuzheng; Wang, Dan; Wang, Tao (Frontiers in Pharmacology, 2024)
Introduction The kidney damage caused by the deposition of uric acid in the kidneys is of urgent need for new treatment drugs due to its complex pathogenesis. Orthosiphon aristatus (Blume) Miq. Also known as C. spicatus, which has a significant therapeutic effect on hyperuricemia nephropathy (HN), however, the specific mechanism of its action is still unknown. Methods The HN mice model was constructed using adenine (AD) and potassium oxonate (PO), and serum biochemical indexes, kidney pathological changes, xanthine oxidase (XOD) activity in the liver, and renal protein expressions of phosphoribose pyrophosphate synthetase (PRPS) and uric acid transporter were detected. The effects of C. spicatus on uric acid lowering, anti-inflammation, and renal protection of HN mice were verified. The effect of C. spicatus on gut microbiota was assessed by 16 S rRNA sequencing. Establish pseudo-sterile mice through the combined treatment of ampicillin, neomycin, and vancomycin to verify the role of gut microbiota in improving HN in C. spicatus. Results In HN mice, C. spicatus could significantly reduce serum uric acid levels and improve renal function. In addition, C. spicatus modulated gut microbiota and decreased the relative abundance of Bacteroides, Prevotellaceae_UCG-001 and Alistipes, and increased the abundance of Alloprevotella and Lachnospiraceae_NK4A136_group.C.spicatus altered the expression of the renal urate transporter and key enzymes in hepatic urate synthesis, leading to a decrease in serum uric acid levels. C. spicatus alleviated kidney inflammation by inhibiting the activation of the NLRP3 and TLR4/MYD88 inflammatory pathways, and reduced the level of kidney inflammatory factors. It also improved kidney damage by inhibiting the process of renal epithelial-mesenchymal transition, and improved kidney fibrosis. In pseudo-sterile HN mice, without the effect of gut microbiota, the uric acid lowering, anti-inflammatory, and renal fibrosis improving effects of C. spicatus were significantly reduced. Conclusion Our results demonstrated that C. spicatus could reduce uric acid levels, anti-inflammatory effects, and improve HN by regulating the gut microbiota. This provides a novel scientific basis for the clinical application of C. spicatus.